Pandangan Pendidikan Islam Terhadap Problematika Rendahnya Mutu Pendidikan di Indonesia - Muthia Zahra; Khairatul Uswah; Gusmaneli, Gusmaneli (CV. ITTC INDONESIA, 2025)
Education is something that is agreed to be a staple in any nation. The quality of education in a nation is one of the determinants of the nation's progress. In other words, the progress of a nation or state can be seen from the quality of education in the nation and country. Basically, the problems that occur in the low quality of education in Indonesia are basically also inherent challenges in the context of Islamic education. This study uses descriptive qualitative research. The method used is literature study. The author collects data and information from reliable journals and books for the truth and in accordance with the discussion of this article. Then with this research, it is hoped that it will be able to find solutions to improve the quality of education in Indonesia which can be reviewed from the perspective of Islamic education.